Discharge and ground electrode design considerations for the lightning strike damage tolerance assessment of CFRP matrix composite laminates. (1st October 2020) - Yousefpour, Kamran; Lin, Wenhua; Wang, Yeqing; Park, Chanyeop
Abstract: Lightning strike damage tolerance of carbon fiber reinforced polymer (CFRP) composites is prone to misinterpretation. This study demonstrates that the design of lightning strike testbeds can be a major cause of the misinterpretation. The risk of misinterpretation originates from the lack of standards clearly defining testbed design requirements including electrode size and ground electrode edge configuration. Here we report the impact of electrode size and ground electrode edge configuration on the damage characteristics of CFRP matrix composite laminates caused by simulated lightning strikes. The results suggest that the level of damage is influenced by discharge current amplitude, discharge diameter, and the existence of electrical insulation covering ground electrode edges. Specifically, the damage increases with increasing discharge current amplitude and decreasing discharge diameter. Most importantly, we report that electrically insulating the edges of ground electrode prevents lightning discharge current from bypassing CFRP matrix composite laminate samples and directly striking the ground electrode. Experiments conducted without electrically insulating the edges resulted in considerably lower sample damages than those resulted from experiments conducted with the electrically insulated ground electrode edges. Our findings suggest that electrode size and ground electrode edge configuration have significant influence on the results of lightning strike experiments.